Quality of prenatal care associated with the incidence of congenital syphilis: integrative review (Research, Society and Development, 2022)
This study aims to analyze the relationship between the quality of prenatal care and the incidence of congenital syphilis in Brazil. This article is an integrative. The databases used were: MEDLINE and LILACS via VHL and Scielo. Twenty articles were selected for the construction of the study. The bibliography surveyed shows that the rate of congenital syphilis in a region indicates the quality of prenatal care offered there. The difficulties faced by pregnant women in accessing syphilis control technologies during prenatal care are highlighted, such as social vulnerability. Adequate prenatal care includes early diagnosis and treatment of Sexually Transmitted Infections such as syphilis of the mother and sexual partner. When this care is not offered, unfavorable outcomes for the neonate occur. Therefore, the importance of this research for Nursing is noted, also emphasizing the need for public policies that bring pregnant women and their partners closer to health services and that promote improvements in prenatal care provided through effective screening and treatment.